Picasso for Preaching: The Demand and Possibility of a Cubist Homiletic - Sunggu Yang (Religions, 2020)
The purpose of this article is to propose a cubist homiletic based on the Picasso-originated art movement known as cubism. To that end, I explore the twofold question: What is cubist preaching, and why do we need it today? It is a critical inquiry into a theology and methodology of cubist preaching and its contextual rationale. In particular, I adopt cubism’s artistic-philosophical routine of transcendental deconstruction and multi-perspectival reconstruction as the key hermeneutical and literary methodology for cubist preaching. This cubist way of preaching ultimately aims for the listener to encounter the Sacred in what I call an ubi-ductive way—a neologism made by conjoining the two terms, ubiquitous and -ductive, beyond what is possible through conventional inductive and deductive preaching.